Analisis Pengelolaan Keuangan Desa di Desa Bojongasih Kabupaten Sukabumi Jawa Barat - Zulkarnain Zulkarnain; Widi Nurdiati (Jambura Accounting Review, 2020)
This study aims to determine the application of Permendagri No. 113/2014 About Village Financial Management About Village Financial Management on Village Financial Management in Bojongasih Village, Parakansalak District, Sukabumi Regency which includes planning, administration, implementation, reporting, accountability, as well as coaching, and overseeing village financial management. The qualitative-descriptive method is used to describe and interpret data on village financial management found in the field and then a conclusion is drawn. Data collection was carried out with documentation and interview studies. Then the data analysis technique is how to reduce, present and verify the data. The results of this study are, in general, financial management of Bojongasih Village, Parakansalak District, Sukabumi Regency, which is not yet fully in accordance with Permendagri Number 113/2014. Some of the obstacles faced by Village Planning include not timely submitting a Raperdes about the Village’s Budget. In the implementation of financial management contrary to Permendagri and not in accordance with Permendagri. Then, monthly reports are not submitted to the Village Head. As well as coaching and supervision from local governments that are less than optimal.